Impact of flash glucose monitoring on glucose control and hospitalization in type 1 diabetes: A nationwide cohort study. Issue 1 (3rd July 2020) - Tsur, Anat; Cahn, Avivit; Israel, Meirav; Feldhamer, Ilan; Hammerman, Ariel; Pollack, Rena
Abstract: Background: We evaluated the impact of flash continuous glucose monitoring (FCGM) on glycemic control and healthcare burden in a large real‐world cohort of patients with type 1 diabetes (T1D) initiating FCGM technology. Methods: In this retrospective cohort study, we included adults (age ≥18 years) with T1D from a large Health Maintenance Organization in Israel, who initiated FCGM during 2018. Primary outcomes included change in HbA1c ≥3 months following FCGM commencement and change in rate of internal‐medicine hospitalization. Additional outcomes included changes in glucose test strip purchases, diabetes related outpatient health care visits and hospitalization for diabetic ketoacidosis (DKA) and/or severe hypoglycemia. Results: The study included 3490 patients, followed for a median of 14 (inter‐quartile range 11‐15) months after FCGM commencement. Among 2682 patients with an HbA1c measured both at baseline and ≥3 months after FCGM initiation, average HbA1c declined from 8.1% ± 1.46% to 7.9% ± 1.31% ( P  < .001) at first measurement and was maintained during follow up. Specifically, in those with HbA1c ≥8%, a mean decline of 0.5% ( P  < .001) was observed. A clinically significant HbA1c reduction of ≥0.5% was experienced by 25.5% of the patients. The rate of internal medicine hospitalization, visits to primary care, or visits to endocrine/diabetes specialists in the period following FCGM commencement vs the 6 months prior was significantly reduced ( P  < .001). Hospitalization for DKA and/or hypoglycemia declined as well ( P = .004). Conclusions: FCGM was associated with significant and durable improvement in glycemic control as well as reduced consumption of healthcare services.